The distance between theoretical and practical leisure activities influenced life satisfaction - Liang Pang; Chengcheng Liu; Yigang Lin; Xinyi Xie, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Recreational activities have acquired the favor and interest of college students and are now essential for their physical and mental well-being. Most activities, including leisure activities, share theoretical and practical elements. This research aims to evaluate a conceptual model about the relationship between leisure attitudes, theoretical and practical leisure, and life satisfaction, as well as to investigate the determinants of life satisfaction. Nine hundred ninety-eight students were sampled and questioned using the "Leisure Values Questionnaire," "Leisure Attitude and Expenses Questionnaire," and "life satisfaction Questionnaire." The outcomes of the primary data were evaluated using a quantitative research strategy based on association and aggressive analysis. The results indicated that the more their preference for leisure activities, the greater their life satisfaction. Those who spend more money and time on leisure activities report greater life satisfaction. Practical leisure was more strongly connected with life satisfaction than theoretical leisure. The predictor for the affective component of life satisfaction was theoretical leisure, while practical leisure was positively associated with the experience component. Meanwhile, positive affect and experience were positively associated with life satisfaction. The study emphasizes the significance of developing a positive attitude toward leisure to increase life satisfaction, supports the significance of leisure favor and practical leisure in achieving life satisfaction, and is helpful for detailed theoretical interpretation and policymakers who develop leisure programs to increase public life satisfaction.